The role of Fas-FasL-FADD signaling pathway in arsenic-mediated neuronal apoptosis in vivo and in vitro. (1st March 2022) - Sun, Hongna; Yang, Yanmei; Gu, Muyu; Li, Yang; Jiao, Zhe; Lu, Chunqing; Li, Bingyu; Jiang, Yuting; Jiang, Lixin; Chu, Fang; Yang, Wenjing; Sun, Dianjun; et al.
Highlights: Excessive arsenic intake has neurotoxic effects. Arsenic induces neuronal apoptosis and ultrastructural damage. Arsenic activates Fas/FasL signaling pathway of nerve cells. ZB4 reverses arsenic-induced apoptosis of SHSY5Y cells. Abstract: The molecular mechanisms underlying arsenic-induced neurotoxicity have not been completely elucidated. Our study aimed to determine the role of the Fas-FasL-FADD signaling pathway in arsenic-mediated neuronal apoptosis. Pathological and molecular biological tests were performed on the cerebral cortex of arsenic-exposed rats and SH-SY5Y neuroblastoma cells. Arsenic induced apoptosis in the cortical neurons, which corresponded to abnormal ultrastructural changes. Mechanistically, arsenic activated the Fas-FasL-FADD signaling pathway and the downstream caspases both in vivo and in vitro. ZB4 treatment reversed the apoptotic effects of arsenic on the SHSY5Y cells. Taken together, arsenic induces neurotoxicity by activating the Fas-FasL-FADD signaling pathway.